Tanggung Jawab Pemerintah Terkait Penonaktifan Peserta PBI Terhadap Kebijakan Surat Keputusan Kementerian Sosial No. 70 Tahun 2019 Tahap Ke Enam - Amalia, Apri; Gunawan Purba, Indra; Sipahutar, Ervina Sari (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
In 2019 the number of poor people ini Medan Citywas 183,790 people with a percentage of the population receiving PBI health insurance of 29,60% based on data from the Central StatisticsAgency. PBI JK participants are people who are classified as poor and cant’t afford whosecontributions are paid by the Government in the amount of Rp. 420.000. In 2091 the Ministry of Social Affairs issued Decree No. 70 0f 2019 sixthphase concerning policies against deactivating PBI JK participants. This is what becomes a polemic ini a society that can’t afford it. The deactivation of thin Center certainly affects PBI participants who hold the Medan Sehat Card in the city of Medan, which provide health protectionbenefits for Medan city residents.The research method uses a normative-empirical research type. The 1945 constitution explicitly stated that the state is obliged to provide health facilities for the poor and is obliged to develop a Social Security System, hence Law no 40. 0f 2004 concerning the National Social Security System and Law no. 24 of 2011 concerning Sosial Security Administering Bodies. Responbility ofthe Medan City Government in collaboration withBPJS Health, the social service and the Medan City Government Hosipital provide and coordinate in carrying out their socialresponbilities for PBI recipients whose assistancehas been stopped by the Minsitry of Social Affairs. BPJS Health as an institution managing guarantees of free health servicer to the poor must coordinate with the Medan city social service as an extension of the government to provide information related to community povertydata ini terms of data management. This coordination is to create order between institutions and the public in the use of law whichfunctions as legal certainty. Keywords: Contribution Assistance Recipients,Health Insurance, Medan City Government